Undercutting Descartes: Jauregui, J A (1995) The emotional computer. Oxford: Blackwell ISBN 0-631-19843-1. xvi+ 304 pages - Henzi, Peter (PINS-Psychology in Society, 2026)
Jose Antonio Jauregui, a social anthropologist by training, profession and inclination, has made an important discovery: the brain is a computer that tells us what to do. Lest this sound overly supercilious, let me add that it is, in context, no trivial point until relatively recently, social anthropologists - not all, but some - argued vigorously for the primacy of culture as the domain in which to analyse human behaviour and, implicitly or explicitly, that humans are rational, freed in some mysterious way from the constraints of biology. As a stance, this attained its polemical height in response, during the 1970s, to the appearance of sociobiology with its reductive claims for human sociality Since then, of course, to the detriment of neither, human sociobiology has matured and anthropology has softened, so that we now see the emergence of robust evolutionary approaches within both psychology and anthropology.